Quality of Life Trajectory and Its Mediators in Older Patients With Acute Decompensated Heart Failure Receiving a Multi-Domain Rehabilitation Intervention: Results From the Rehabilitation Therapy in Older Acute Heart Failure Patients Trial. (8th November 2022) - Whellan, David; McCarey, Melissa M.; Chen, Haiying; Nelson, M. Benjamin; Pastva, Amy M.; Duncan, Pamela; Mentz, Robert J.; Kitzman, Dalane W.; Reeves, Gordon; Reed, Shelby D.
Abstract : Background: As patients with heart failure experience worsening of their condition, including acute decompensated heart failure, quality of life deteriorates. However, the trajectory of quality of life changes and their determinants in the context of the Rehabilitation Therapy in Older Acute Heart Failure Patients trial physical rehabilitation intervention are unknown. Methods: Patients ≥60 years old admitted for acute decompensated heart failure (n=349) were randomized to either attention control or intervention. Quality of life outcomes (Kansas City Cardiomyopathy Questionnaire; 12-Item Short-Form Health Survey) were measured at baseline (inpatient), 1 month, and 3 months. Intervention effects were assessed using linear mixed effects regression, including covariates to model the main effects of the intervention and timing of outcome assessments. Mediation analysis determined if changes in Kansas City Cardiomyopathy Questionnaire were due to improvement in physical function (short physical performance battery, 6-minute walk distance). Results: Baseline Kansas City Cardiomyopathy Questionnaire summary score was similarly poor in the intervention and control arms (40.2±20.6 versus 41.5±20.6). Although the intervention experienced nominally greater Kansas City Cardiomyopathy Questionnaire improvement than control at 1 month (64.7±1.9 versus 61.1±1.9, P =0.13), the difference was not statistically significant until 3 months (67.7±1.9 versus 60.8±1.9, P =0.004). Twelve-Item Short-Form Health Survey Physical and Mental Composite Scores increased in both arms at 1 month and continued improvement only in the intervention. The 3-month improvement in short physical performance battery score explained 64.1% of the improvement in Kansas City Cardiomyopathy Questionnaire ( P <0.001). Conclusions: In older patients hospitalized for acute decompensated heart failure, quality of life improves in the first month after discharge. The quality of life benefit of a post-discharge physical rehabilitation intervention is detected early with large significant improvements at 3 months achieved primarily through improvement in short physical performance battery. Registration: URL: https://clinicaltrials.gov ; Unique identifier: NCT02196038.